(untitled) (Global Journal of Management and Business Research, 2022)
People are afraid to come out of their houses due to Covid-19. Physical socializing and interaction with other people has become a threat to life and people are moving towards the virtual ways of interacting with people. This has become a bane for hospitality industry. But still restaurants and hotels are taking necessary precautionary measures for the safety of the guests.